'Solidarity, Sisters! We're All Crazy': The Moral Madness of Opting Out of High-Stakes Testing. Issue 4 (3rd July 2020) - Schroeder, Stephanie; Currin, Elizabeth; McCardle, Todd
Abstract: This article explores how moral madness manifests in the Opt Out Florida Network, a group committed to ending high-stakes standardized testing. Using data culled from a critical online ethnography of the movement, we show how parents and teachers in the Opt Out Florida Network experience moral madness as a result of standardization and high-stakes accountability in U.S. schools. Our findings, positioned within the neoliberal policy environment, reflect a larger state of crisis in the education profession, wherein both teachers and parents find their autonomy and expertise devalued. Repositioning our participants' madness as moral injury, we recommend democratic pathways to healing.